Menghayati Selibat sebagai Sebuah Anugerah dalam Menghadapi Tantangan Dewasa Ini - Agut, Yoseph Selvinus (Media: Jurnal Filsafat dan Teologi, 2025)
This article represents a literature review focusing on the concept of celibacy within the Catholic Church. Celibacy, a longstanding tradition within the Church, has been carefully preserved over the centuries. Numerous studies have highlighted the various challenges that celibacy faces, such as spiritual desolation, clericalism, and incidents of clerical sexual misconduct. These obstacles raise questions regarding the legitimacy of celibacy and how it can be maintained within the Church. The central inquiry addressed in this article pertains to comprehending the dynamics of celibacy as a divine gift and how individuals can uphold this choice amidst contemporary challenges. The gift of celibacy profoundly influences every facet of a person's identity and emotional well-being. It is not to be viewed through conventional societal norms, but rather as a manifestation of God's will within the celibate individual's unique circumstances, serving as a testament to their faith. Consequently, the commitment to celibacy must be undertaken willingly, with a continuous dedication to maintaining fidelity, transparency, and accountability in order to effectively fulfill one's ministry.